2023
DOI: 10.21037/tlcr-22-619
|View full text |Cite
|
Sign up to set email alerts
|

Advancements of ALK inhibition of non-small cell lung cancer: a literature review

Abstract: Background and Objective The therapeutic landscape for non-small cell lung cancer (NSCLC) has evolved considerably in the last few years. The targeted drugs and molecular diagnostics have been developed together at a fast pace. This narrative review explores the evolution of anaplastic lymphoma kinase (ALK) targeting therapies from discovering the ALK protein, molecular tests, present clinical trial data and future perspectives. Since the body of evidence on lung cancer is growing daily, most onco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 49 publications
(102 reference statements)
0
4
0
Order By: Relevance
“…This prolonged PFS is anticipated to transform the disease into a manageable, chronic condition. Effective treatment sequencing will be vital for patient survival, and the potential replacement of tissue biopsies with liquid biopsies is on the horizon [156]. In addition, clinical trials have shown that ALK inhibitors exhibit excellent efficacy against brain metastases.…”
Section: Alk and Co-targeting Approachesmentioning
confidence: 99%
“…This prolonged PFS is anticipated to transform the disease into a manageable, chronic condition. Effective treatment sequencing will be vital for patient survival, and the potential replacement of tissue biopsies with liquid biopsies is on the horizon [156]. In addition, clinical trials have shown that ALK inhibitors exhibit excellent efficacy against brain metastases.…”
Section: Alk and Co-targeting Approachesmentioning
confidence: 99%
“…Furthermore, the Asian population-based ALESIA study showed even better efficacy, with an mPFS of 41.6 months and an ORR of 91%. However, despite the significant clinical benefits achieved with alectinib, resistance to alectinib occurred in 53.3% of patients treated with alectinib as the first-line therapy, leading to disease progression, and more progressive disease occurred in second-line alectinib treatment ( 4 , 15 - 17 ). ALK-TKIs resistance mainly arises from ALK mutations and ALK amplification, such as the G1202R mutation ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, tyrosine kinase inhibitors targeting epidermal growth factor receptor (EGFR) mutations have dramatically improved the typical prognosis of advanced NSCLC from 12-14 months to 36-48 months [5][6][7][8]. Consequently, the identification of such mutations like anaplastic lymphoma kinase (ALK) [9], ROS proto-oncogene 1 (ROS1), V-raf murine sarcoma viral oncogene homolog B1 (BRAF) [10], MET proto-oncogene, receptor tyrosine kinase (MET) [11], and RET proto-oncogene receptor tyrosine kinase (RET) [12] has become increasingly critical in routine clinical practice.…”
Section: Introductionmentioning
confidence: 99%